Study on Variation of Equilibrium Constant as a Function of Ionic Size in Some Uni-Univalent Ion Exchange Systems - Lokhande, R.S.; Singare, P.U. (Asian Journal of Chemistry, 2010)
Ion exchangers in chloride form were equilibriated with potassium iodide and potassium bromide solutions of different concentrations and at different temperatures from 30-45oC. The equilibrium constant (K) values for both exchange reaction were observed to increase with increase in temperature. However the equilibrium constant (K) for Cl-/Br- exchange at 30°C was 1.16 which was less than 16.70 for Cl-/I- exchange at the same temperature which was due to difference in ionic size of iodide (2.20 Å) and bromide (1.96 Å) ion exchanged.